If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4y + 3 + -3y = 6 Reorder the terms: 3 + 4y + -3y = 6 Combine like terms: 4y + -3y = 1y 3 + 1y = 6 Solving 3 + 1y = 6 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 1y = 6 + -3 Combine like terms: 3 + -3 = 0 0 + 1y = 6 + -3 1y = 6 + -3 Combine like terms: 6 + -3 = 3 1y = 3 Divide each side by '1'. y = 3 Simplifying y = 3
| 3r^2+2r-3=0 | | 5n+1/8=3n-5/4 | | -7x-5=-33 | | -1(3-10y)=12 | | 5p-7=2p-4 | | 4g+6=2g+14 | | 4x^2+16x-15=0 | | t+(-14)= | | 7-4*x=13 | | -4y+7=-21 | | 3b-4=5b-2 | | 9-5n=30 | | 4(b-2)=2(b-6) | | 7x-(4x-6)=30 | | 6r-(-2r-27)=21 | | 19-4c= | | 18=10+4x+4 | | 6y-2=14y+62 | | 7x+9=-29 | | 9=x-3 | | 6y-2=14y+64 | | 3h+1=3(h+1) | | 7x-7=49 | | 2(x-1)-3(x+2)=8 | | 8(12)-18=n | | y=.03x+200 | | -6x-1=-1 | | 3(x-5)=6(x-6) | | 14x+23=-93 | | 7x+3(4x-1)=49 | | 12-8x-6=-13x+21 | | -3x-10=-10 |